IIO MODEL IN LEARNING SECOND/ADDITIONAL LANGUAGE - Yosi Handayani (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
This paper summarizes a range of theoretical reviews about language and learning language and how important the role of language input to the success of the learners. Learning language used to be focused on the syntax or sentence structure, which is no longer the answer of learning an additional language (AL) or Second Language (SL). The complexity of language and the learners automatically make the language learning become a complex subject and complex study. There some aspects inside the learners which influence the language learning process. The notion of interlanguage of the learners is also an important process to be analysed by the teachers. Input Interaction and Output (IIO) model is one which can present information about the complexity of the language process.  Therefore, this essay will describe how the theories about input, interaction, and output can work well in the practice of SL or AL learning class. This essay will also discuss how the linguistic and conversational adjustments of the teacher, as well as the modification of the interactional structures help better out put in the language learning.